Analisis Penyelenggaraan Penataan Ruang Dalam Perspektif Pembangunan Berkelanjutan Di Kabupaten Lampung Timur - Lintje Anna Marpaung (PRANATA HUKUM, 2014)
Utilization of space that is not appropriate with the spatial planning could threaten environmental sustainability. The implementation of transparent spatial planning, effective, and participatory required in order to realize safe area, comfortable, productive, and sustainable for peopleâs welfare. The main problem in implementating this research include, how the implementation of spatial planning in the perspective of sustainable development in East Lampung Regency. Implementation of spatial planning in order to achieve the orderly use of space in East Lampung Regency has not been optimally implemented and inhibiting factors of implementation regional regulation of spatial plan comes from internal factors and external factorsÂ of local government. Internal factors consists of spatial planning is still general, lack of human resources and funding to carry out surveillance, lack of understanding of government officials, government officials do not quite have the courage to impose sanction, lack of socialization and counseling to the community.